Fasting Induces IL-1 Resistance and Free-Fatty Acid-Mediated Up-Regulation of IL-1R2 and IL-1RA - Joesting, Jennifer J.; Moon, Morgan L.; Gainey, Stephen J.; Tisza, Brittany L.; Blevins, Neil A.; Freund, Gregory G. (Frontiers in Immunology, 2014)
Objective: Weight loss is a near societal obsession and many diet programs use significant calorie restriction (CR) including fasting/short term starvation to generate rapid effects. Fasting is also a well-recognized cause of immunosuppression especially within the innate immune system. In this study, we sought to determine if the IL-1 arm of the neuroimmune system was down-regulated by a 24 hr fast and how fasting might generate this effect. Design: Mice were allowed ad libitum access to food or had food withheld for 24 hrs. Expression of the endogenous IL-1 antagonists IL-1 receptor type 2 (IL-1R2) and IL-1 receptor antagonist (IL-1RA) were determined as were sickness behaviors before and after IL-1 administration. Results: Fasting markedly increased gene expression of IL-1R2 (83-fold in adipose tissue, 9.5-fold in liver) and IL-1RA (68-fold in liver). Fasted mice were protected from IL-1-induced weight loss, hypoglycemia, loss of locomotor and social anxiety. These protections were coupled to a large positive interaction of fasting and IL-1 on IL-1R2 gene expression in adipose tissue and liver (2.6-fold and 1.6-fold, respectively). Fasting not only increased IL-1RA and IL-1R2 protein 2.5-fold and 3.2-fold, respectively, in liver; but also increased IL-1R2 1.8-fold in adipose tissue. Fasting, in turn, triggered a 2.4-fold increase in plasma free-fatty acids (FFAs) and a 2.1-fold increase in plasma corticosterone. Inhibition, of glucocorticoid action with mifepristone did not impact fasting-dependent IL-1R2 or IL-1RA gene expression. Administration of the FFA, palmitate, to mice increased liver IL-1R2 and IL-1RA gene expression by 14-fold and 11-fold, respectively. Conclusion: These findings indicate that fasting augments expression of endogenous IL-1 antagonists inducing IL-1 resistance. Fasting-induced increases in plasma FFAs appears to be a signal that drives immunosuppression during fasting/short term starvation.